DISCLOSING BEHIND MOSQUE AND MUSALLA LOUDSPEAKER POLICY REPORT: ANALYSIS OF KOMPAS.COM AND DETIK.COM - M Iqbal Sultan; Bono Setyo; Lelita Azaria Rahmadiva (Profetik: Jurnal Komunikasi, 2023)
Mosques and Musalla Loudspeakers Policy, and the analogy of the azan with barking dogs by the Minister of Religion, Yaqut Cholil Qoumas has drawn pros and cons from various party. The pros and cons are inseparable from the influence of online news media. This study tries to answer questions related to news tendencies and the background of the pros and cons of the Policy Guidelines for Using Loudspeakers in Mosques and Musalla. This study analyzes news related to Mosques and Musalla's loudspeaker Policy on the two most influential online news media in Indonesia based on SEMRUSH, namely Kompas.com, and Detik.com. Content analysis is used for this study, carried out two weeks after the policy was issued, from February 21 to March 6, 2022. The study results found that The informant's affiliation greatly contributes to providing a pro or con statement. News tendency is influenced by who and what interests are behind these two big media. This reporting trend is shown through the appointed Informants, the titles and narratives presented, and the topics of news discussion. The causes of the pros and cons of the Minister of Religion's policy are due to differences in perceptions in interpreting the policies and statements of the Minister of Religion Yaqut Cholil Qoumas by the informants.